The Role of Management Information Systems in Improving Performance (Study at SMP Negeri 2 Ampana Tete) - Andi Indriani Ibrahim; Nurwasilah Lanonci; Miftahul Jannah; Yusriyani Herawaty; Nini Andriani; Ayu Putri Utami (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to describe the role of management information systems in improving school performance from the aspects of transparency and accountability at SMP Negeri 2 Ampanan Tete. The method used is a qualitative method with a descriptive approach, the technique of collecting data through direct interviews. The results showed that SIM is very important to speed up and facilitate access to information, enable more systematic reporting, and improve supervision and evaluation of academic and administrative performance. To address these issues, a broad approach is needed, including increased technology training, effective change management, and the creation of strong data security protocols. This study shows how important SIM is to support transparency and accountability at SMP Negeri 2 Ampana Tete school. In addition, it also provides suggestions on how to implement it better.